Differences in Oral Health-Related Quality of Life (OHRQoL) among the Elderly Population in Rembang Regency - Shafira Nur Amalia Zulva; Avina Anin Nasia; Setyo Gundi Pramudo; Yosef Purwoko (Faculty of Dentistry, Universitas Gadjah Mada, 2022)
Epidemiological studies have shown that several factors, such as age, gender, tooth loss, socioeconomic status, cultural background, psychological stress of dental visit, and smoking can influence OHRQoL. Oral health is strongly age dependent, therefore OHRQoL differences are predicted to exist in the elderly group according to WHO. This condition is especially true for Rembang Regency due to the high population of the elderly and the shared ignorance on oral health given an overemphasis on other priorities, which will have an impact on their quality of life. The objective of this study is to know the OHRQOL difference in the elderly group in Rembang Regency with cross-sectional design. The research subjects were selected by inclusion and exclusion criteria with online informed consent. The questionnaire related to age and GOHAI was distributed and filled out online. Data were processed and analyzed using the Kruskall Wallis followed by Mann-Whitney post-hoc analysis and multiple linear regression test. A total of 222 respondents were involved (n= 222) consisting of 102 male and 120 female. The majority level of their OHRQoL were moderate (65.3%). The most affected dimension was physical function since it limits the type or amount of food intake (30.4%). The Kruskall-Wallis test showed significant OHRQoL differences in middle-age, elderly, old, and very old groups (p<0.05). The OHRQoL difference between middle-age and old and middle-age and very old obtained a significant result in the Mann-Whitney post hoc test with p value <0.05. Multiplelinear regression test showed a significant effect of age on OHRQoL with tooth loss as a confounding variable. Thus, Oral Health Related Quality of Life (OHRQoL) of the elderly group is significantly different.